Privacy-aware personal navigation services / Melissa Shahrom - Shahrom, Melissa (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Location privacy is a growing area of social concerns. Mobile devices are rapidly evolving into multipurpose devices that can access a wide range of services with location-aware features such as navigation systems. While navigation systems and location-aware services are essentials, the services are easily exposed to intruders. Therefore, protecting the confidentiality of location privacy is extremely vital. This innovation produces an algorithm that is able to protect location privacy and at the same time generate robust navigation instructions without depending on precise location information. With this technique, location information and data stored on location-based applications will be highly protected.